Arabic and Semitic studies at Sofia University and the shifting interactions of Bulgaria with the Middle East and Islam (Philology, 2026)
The Orient-Institut Beirut (OIB) in cooperation with the Department of Arabic and Semitic Studies at Sofia University St. Kliment Ohridski held a three-day workshop within the activities of the international research project “Relations in the Ideoscape: Middle Eastern Students in the Eastern Bloc (1950’s to 1991) on 22 – 24 July 2021.